RELATIONSHIP BETWEEN ARTERIAL STIFFNESS, PHYSICAL ACTIVITY & SEDENTARY TIME IN A YOUNG MIDDLE-EASTERN POPULATION. (April 2021) - Mahmud, Azra; Dalton, Teigh; Nalin, Jay; Nalin, M.; Merrigan, Orla; Saud, Anas; Hamadah, Randah
Abstract : Objective: Arterial stiffness (AS) and physical activity are independent cardiovascular(CV) risk factors and predict outcome. We and others have shown that PA is associated with AS; however, the data is largely derived from older, Caucasian populations assessing PA with questionaires. The aim of this study was to explore the relationship between AS and PA using actigraphy in a young Middle-Eastern population, hitherto not studied. Design and method: Four-hundred and two apparently healthy subjects (mean age 20.7 ± 3 years, 52% females) were enrolled in this cross-sectional study. Anthropometric measurements performed included weight, height, waist and hip, total body fat, visceral fat and muscle mass. Participants received an accelerometer (ActiGraph™) to wear on the wrist for 7 consecutive days. The average minutes/day spent at different PA intensities (min/day) was determined according to established cut-points as well as metabolic equivalents (METS). Arterial stiffness was measured using the SphygmoCor™ and Mibilograph® as pulse wave velocity (PWV), central BP and augmentation index(AIx), after fifteen minutes of supine rest. The data was analysed using JMP Pro version 13 (SAS for Windows, NC, USA). Results: 30% of the population met the AHA Guidelines for PA with no gender difference. None of the subjects achieved moderate-vigorous or very vigorous activity with almost 50% of the time spent in being sedentary. There was a significant association between daily step count and body fat and body muscle content (p < 0.001). PWV was associated with age (r = 0.25, p < 0.001), brachial systolic BP(r = 0.57, p < 0.0001), aortic systolic BP(r = 0.65, p < 0.0001), cardiac output(r = 0.39, p < 0.0001), METS achieved(r = -0.42, p < 0.0001), light activity (r = -0.25, p < 0.001), moderate-to-vigorous (r = -0.29, p < 0.001), sedentary time (r = 0.45, P < 0.0001), waist(r = 0.47, p < 0.0001), visceral fat(r = 0.39, p < 0.001) and muscle mass(r = -0.31, p < 0.01). In a stepwise regression model with PWV as the dependent variable, age, MAP, gender, METS achieved and sedentary time emerged as independent determinants of PWV (R2 = 0.39, p < 0.0001). Conclusions: Unhealthy life-style is a strong risk factor for CVD, partly through the development of premature arterial stiffening. Our results highlight the deleterious effects of sedentary time on vascular function, independent of physical activity and energy consumption in a young, healthy population.